Evaluation of viability and effectiveness of restricted-use protected areas in the Ceará, Brazil - Aguiar-Silva, Francisca Helena; Bonilla, Oriel Herrera; Nascimento, Camylla Alves (Revista Caatinga, 2011)
We analyzed the viability and effectiveness of restricted-use protected areas aiming to identify gaps in the definition of priorities to protect wild regions from Ceará. Based on the creation of legal documents and interviews with managers of protected areas, we analyzed the size, we verified the existence of the management plan, monitoring activities and the criteria used in selecting the area. We found that in eight of the sixteen protected areas had not followed technical-scientific criteria, nor had carried through previous studies of the resources when they had chosen the areas to be transformed into completely protected areas. Fifteen do not possess management plans and 13 do not have environmental monitoring activities. Eleven protected areas have less than 10,000 ha, and insufficient studies that accurately ascertain the extent appropriate to maintain the biodiversity of the ecosystems of Ceará. It is necessary to deploy tools for maintaining these forests to protect the wildlife and the environmental services provided by these areas.
Avaliação da viabilidade e efetividade das unidades de conservação de proteção integral no Ceará, Brasil